Optimization of production strategies for African indigenous trees: a case study of tree growers and sellers of Dovyalis caffra (Kei apple) from Eastern Cape of South Africa - Mfini, M.; Laubscher, C. P.; Witbooi, H. (Frontiers in Food Science and Technology, 2025)
Dovyalis caffra commonly known as Kei apple, is an indigenous tree from the Salicaceae family, naturally found in the Eastern Cape region of South Africa, with a significant potential to address food insecurity and climate resilience challenges in rural areas. This review aims to evaluate the production potential, uses, and socio-economic contributions of D. caffra, focusing on optimizing its cultivation and market integration through indigenous knowledge and agroforestry system. The research was conducted in the Eastern Cape province of South Africa. Research was conducted using online databases such as ResearchGate, PubMed, and Google Scholar, focusing on keywords like “food security,” “Dovyalis caffra,” and “indigenous trees.” Secondary data was gathered from previous studies, and conclusions were drawn from related research. Additionally, a case study involved interviews with five tree growers/sellers in the Eastern Cape, assessing the challenges and benefits of cultivating and marketing D. caffra. Findings revealed that some growers are motivated to promote Indigenous species, recognizing the economic and ecological benefits of cultivating Kei apple. The tree’s resilience to climate change, soil degradation, water scarcity, and pest infestations makes it a promising alternative to traditional crops. Additionally, its cultivation can diversify food sources and enhance community resilience. Promoting indigenous trees like D. caffra through agro processing can maximize their economic value while supporting local communities and sustainable forestry practices.